Science Technology, Engineering, Art & Mathematics (STEAM) exhibition / Dr Norkasihan Ibrahim ... [et al.] - Ibrahim, Norkasihan; Ishak, Nor Zaleha; Abdul Rahman, Hizwan Nizam; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On Wednesday 21 June 2023, the Faculty of Pharmacy UiTM, along with other exhibitors from the College of Engineering Studies, College of Creative Arts Studies, College of Architecture, and The Faculty of Health Sciences, took part in the +ICAN STEAM Outreach Program, which was held at SMK Serendah in Rawang. The program was organized by the Office of Community, Industry, and Alumni Network (ICAN) UiTM aimed to provide awareness and knowledge transfer of Science, Technology, Engineering, Arts, and Mathematics (STEAM) targeting 200 students in Form 1 to Form 5. The opening ceremony was attended by the school principal, Director of Industry Network Centre (INC), Professor Dr. Muhammad Hussin Ismail, members of the ICAN Office UiTM and the Faculty of Pharmacy Deputy Dean of ICAN, Dr. Norkasihan Ibrahim. The faculty team, led by Puan Nor Zaleha Ishak and Dr Nor Azma Jusoh@Yusof showcased the Do-It-Yourself Soap and Maker-Lab stations. The rest of the team comprised of members from the Pharmaceutics, Pharmacology and Chemistry departments, as well as volunteers from faculty post-graduate students. The DIY Soap station provided students with the opportunity to create olive oil soaps that were personalised with their choice of colour, aroma, and design.